Analysis of Functions and Semiotic Meanings of Traditional Acehnese House Ornaments - Helmi, Rahil (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2023)
Aceh has a unique and distinct cultural heritage as one of the ethnic groups in Indonesia. This study attempts to analyze the functions and meanings of signs and symbols in Aceh Houses (Rumoh Aceh) using the triangle theory proposed by Peirce. The research method used in this study involves interpreting field and literature data obtained. The interpretation process is based on local references derived from the social and cultural values prevalent in Acehnese society. Data is collected through documentation and several previous scientific publications. The data is then analyzed using a Peircean semiotic approach. The research findings indicate that the signs present in Rumoh Aceh are closely related to religious elements, positioned in buildings oriented from east to west (facing the qibla), rooms divided into three spaces serving as private and non-private areas, and demarcating spaces between men and women. The architectural design and elevation of the building from the ground carry the meaning of protection from natural elements such as wild animals and floods. Ornamental motifs of flora and fauna are employed to preserve nature and coexist with living creatures, both animals and plants. Religious motifs aim to remember and draw closer to the divine. A variety of colors symbolize the characteristics and culture of Acehnese society. The use of various carved motifs signifies the homeowner's social strata.